PERTANGGUNGJAWABAN PIDANA TERHADAP KECELAKAAN KAPAL AKIBAT TIDAK LAIK LAUT - Vicky Hanggara Alexandro; Mety Rahmawati (Fakultas Hukum Universitas Tarumanagara, 2018)
Sea voyage is an important part for an archipelagic country like Indonesia to fulfill the people needs, either it’s the main needs or supporting needs. The use of ships in Indonesia should be the main attention. Indonesia has regulate Undang-Undang Nomor 17 Tahun 2008 tentang Pelayaran, and many more regulations that regulate all matters relate to water transportation for goods and people. In practice of the law and the regulations that regulate the function and duty for each parties along with their responsibilities, that either directly related or not in the ship’s operation. However, it doesn’t create a secure and controlled conditions with the result that many ships in Indonesia are drowned, burn out, crash that casualties have taken many life as happened to KM Zahro Express, were drowned because the ship was not seaworthy to be operated, nevertheless the captain still sailed the ship, in this case the caption is blamed for, but in terms of seaworthy, not only the caption that is responsible but also the ship owner and the syahbandar take parts of the responsibilities. The questions which arise from this case is that how is the criminal liability of the ship owner towards a ship accident? The method that is being use in this study is normative research method and strengthened with data and interviews. Study data shows that in ship accident not only the caption that is responsible but also the syahbandar and the ship owner have the same responsibilities for the ship accident.